Tetrahedral Tetraphosphonic Acids. New Building Blocks in Supramolecular Chemistry - Schuetrumpf, Alexandra; Kirpi, Erdogan; Bulut, Aysun; Morel, Flavien L.; Ranocchiari, Marco; Lork, Enno; Zorlu, Yunus; Grabowsky, Simon; Yucesan, Gundog; Beckmann, Jens (AMER CHEMICAL SOC, 2015)
The structural characterization of tetraphenylmethane tetrakis-4-phosphonic acid (4a) and its closely related Si-analogue tetraphenylsilane tetrakis-4-phosphonic acid (4b) is reported. Crystals of 4a, obtained by crystallization at 165 degrees C from water under hydrothermal conditions, comprise a dense threefold interpenetrated hydrogen-bonded network. Lower calculated density cocrystals 4b.4 EtOH, attained by recrystallization from ethanol, give rise to a porous honeycomb network that shows no interpenetration. Isolated from the mother liquor, the encapsulated ethanol is rapidly lost under ambient conditions leaving amorphous 4h. While the amorphous 4b is reasonably soluble in methanol, crystalline 4a is virtually insoluble in common organic solvents.
Keywords: METAL-ORGANIC FRAMEWORKS; STATE COORDINATION CHEMISTRY; SOLID-STATE; INTERMOLECULAR INTERACTIONS; PHOSPHONATE CHEMISTRY; STRUCTURAL CHEMISTRY; CRYSTAL-STRUCTURES; VOID CHANNELS; NETWORKS; DESIGN; Chemistry; Crystallography; Materials Science